Behavioral response of three subterranean pests (Agriotes lineatus, Diabrotica virgifera virgifera, Phyllopertha horticola) to the fungal volatile organic compounds 1-octen-3-ol and 3-octanone - Pierre-Antoine Bourdon; Maria Zottele; Zeeshan Zafar; Ian Baxter; Audun Midthassel; Arben Myrta; Katharina F. Wechselberger; Hermann Strasser; Tariq M. Butt (Arthropod-Plant Interactions, 2023)
The volatile organic compounds (VOCs) 1-octen-3-ol and 3-octanone produced by the entomopathogenic fungus Metarhizium brunneum are known to have pesticidal properties at high doses against a range of invertebrate pests. Very little is known about their behavior-modifying (semiochemical) properties. This study focused on investigating the behavioral responses of three subterranean crop pests, wireworm ( Agriotes lineatus ) , western corn rootworm ( Diabrotica virgifera virgifera ), and garden chafer ( Phyllopertha horticola ), to relatively low doses of 1-octen-3-ol and 3-octanone. The behavior of wireworms and corn rootworms were slightly influenced by the VOCs, yet not significantly. Western corn rootworms appeared to be slightly attracted by 100 µl and 200 µl 1-octen-3-ol and 100 µl dose of 3-octanone, respectively but slightly repelled by the higher dose of 3-octanone. Wireworms appeared to be slightly repelled by 1-octen-3-ol and high dose 3-octanone, but slightly attracted by the 100 µl dose of 3-octanone. The VOCs had no significant impact on garden chafer. In silico studies showed that corn rootworm odorant binding proteins (OBPs) had a strong binding affinity of 1-octen-3-ol and high dose 3-octanone, indicating that these VOCs can be detected and recognized by corn rootworm. OBPs are well conserved between species; thus, wireworm and garden chafer OBPs should also be able to bind with the VOCs. Further trials will be done to confirm that VOCs could be used as semiochemicals. Appropriate formulation of the VOCs should increase their efficacy and prevent rapid dissipation of the VOCs.